Treating Irrigation Systems with Chlorine - Kati W. Migliaccio; Brian Boman; Gary A. Clark; Allen G. Smajstrla (EDIS, 2009)
Revised! Circular 1039, a 7-page illustrated fact sheet by Kati W. Migliaccio, Brian Boman, and Gary A. Clark, provides a guide for using chlorine to treat inhibiting microorganism buildup in irrigation systems. Includes references. Published by the UF Department of Agricultural and Biological Engineering, May 2009.